In Vitro Schistosomicidal Activity of Balsaminol F and Karavilagenin C - Ramalhete, Cátia; Magalhães, Lizandra G.; Rodrigues, Vanderlei; Mulhovo, Silva; Da Silva Filho, Ademar A.; Ferreira, Maria-José U. (Planta Medica, 2012)
Five cucurbitane-type triterpenes (1–5), previously isolated from the African medicinal plant Momordica balsamina, along with five ester derivatives (6–10) of karavilagenin C (2), were evaluated for their potential schistosomicidal activity against Schistosoma mansoni adult worms. The natural compounds were isolated from the ethyl acetate-soluble fraction of the methanol extract of the aerial parts of M. balsamina. In a preliminary study, a significant schistosomicidal activity was observed for both the crude methanol extract and the ethyl acetate fraction. The compounds responsible for the activity were found to be balsaminol F (1) and karavilagenin C (2) with LC50 values of 14.7 ± 1.5 and 28.9 ± 1.8 µM, respectively, after 24 h of incubation (positive control praziquantel, LC50 = 1.2 ± 0.1 µM). Both compounds (1, 2), at 10–50 µM, induced significant reductions in the motor activity of the worms and significantly decreased the egg production. Furthermore, they were able (at 10–100 µM) to separate the adult worm pairs into male and female after 24 h. Compounds 3–5, bearing a sugar moiety as a substituent, and the acylated derivatives of karavilagenin C (6–10) were inactive, suggesting that the presence of free hydroxyl groups in the tetracyclic skeleton might be important for the activity. A correlation between activity and the molecular volume/weight of compounds was also found.
Keywords: schistosomicidal activity; Schistosoma mansoni; Momordica balsamina; Cucurbitaceae; cucurbitane-type triterpenoids